IL‐3 up‐regulates and activates human eosinophil CD32 and αMβ2 integrin causing degranulation. Issue 4 (23rd January 2017) - Esnault, S.; Johansson, M. W.; Kelly, E. A.; Koenderman, L.; Mosher, D. F.; Jarjour, N. N.
Summary: Background: Eosinophils contribute to the pathogenesis of multiple diseases, including asthma. Treatment with antibodies targeting IL‐5 or IL‐5 receptor α reduces the frequency of asthma exacerbations. Eosinophil receptors for IL‐5 share a common ß‐chain with IL‐3 and GM‐CSF receptors. We recently reported that IL‐3 is more potent than IL‐5 or GM‐CSF in maintaining the ERK/p90S6K/RPS6 ribosome‐directed signaling pathway, leading to increased protein translation. Objective: We aimed to determine disease‐relevant consequences of prolonged eosinophil stimulation with IL‐3. Results: Human blood eosinophils were used to establish the impact of activation with IL‐3 on IgG‐driven eosinophil degranulation. When compared to IL‐5, continuing exposure to IL‐3 further induced degranulation of eosinophils on aggregated IgG via increased production and activation of both CD32 (low affinity IgG receptor) and αMß2 integrin. In addition, unlike IL‐5 or GM‐CSF, IL‐3 induced expression of CD32B/C (FCGRIIB/C) subtype proteins, without changing CD32A (FCGRIIA) protein and CD32B/C mRNA expression levels. Importantly, these in vitro IL‐3‐induced modifications were recapitulated in vivo on airway eosinophils. Conclusions and Clinical Relevance: We observed for the first time upregulation of CD32B/C on eosinophils, and identified IL‐3 as a potent inducer of CD32‐ and αMß2‐mediated eosinophil degranulation.